Development of the library at SMA Negeri 15 Bandung through the P3KNK internship program - Adika Subangkit; Davina Putri Ainny; Muhammad Rifqi Ibrahim (Universitas Pendidikan Indonesia, 2025)
School libraries play a crucial role in supporting the learning process by providing relevant and accurate sources of information. Program Penguatan Profesional Kepustakawanan Non Kependidikan (P3KNK) or internship program for Students from the Library and Information Science Program at Universitas Pendidikan Indonesia (UPI) at SMA Negeri 15 Bandung Library aims to provide practical work experience for students while supporting the development of the library through service innovations, collection management, and digital-based promotion. This community service is conducted to address various challenges the library faces, such as limited collections, low library utilization, and manual administrative systems. The method used in this service is a descriptive qualitative approach, with data collection through observation, interviews, and documentation. The findings of this service show that the internship program successfully improved the library's service quality through implementing information technology (SLiMS), collection processing, and effective promotion using social media. However, several challenges, such as limited time, lack of collection diversity, and a fully digital administrative system, still need to be addressed. This program has positively contributed to the library's operations and provides recommendations for further improvements, such as digitizing the circulation system and expanding the variety of book collections. Abstrak Perpustakaan sekolah memiliki peran penting dalam mendukung proses pembelajaran dengan menyediakan sumber informasi yang relevan dan akurat. Program Penguatan Profesional Kepustakawanan Non Kependidikan (P3KNK) dari Program Studi Perpustakaan dan Sains Informasi Universitas Pendidikan Indonesia (UPI) di Perpustakaan SMA Negeri 15 Bandung bertujuan untuk memberikan pengalaman praktis kepada mahasiswa serta mendukung pengembangan perpustakaan melalui inovasi layanan, pengelolaan koleksi, dan promosi berbasis digital. Pengabdian ini dilakukan untuk mengatasi berbagai tantangan yang dihadapi oleh perpustakaan, seperti keterbatasan koleksi, rendahnya pemanfaatan perpustakaan, dan sistem administrasi yang masih manual. Metode yang digunakan dalam pengabdian ini adalah pendekatan deskriptif kualitatif, dengan pengumpulan data melalui observasi, wawancara, dan dokumentasi. Temuan dari pengabdian ini menunjukkan bahwa program magang berhasil meningkatkan kualitas layanan perpustakaan melalui penerapan teknologi informasi (SLiMS), pengolahan koleksi, dan promosi yang efektif menggunakan media sosial. Namun, beberapa kendala seperti keterbatasan waktu, kurangnya variasi koleksi, dan sistem administrasi yang belum sepenuhnya digital masih perlu diperbaiki. Program ini memberikan kontribusi positif terhadap operasional perpustakaan dan memberikan rekomendasi untuk perbaikan lebih lanjut, seperti digitalisasi sistem sirkulasi dan penambahan variasi koleksi buku. Kata Kunci: digitalisasi perpustakaan; magang perpustakaan; manajemen koleksi; promosi perpustakaan; SLiMS